Effects of l-arginine and l-histidine on heat-induced aggregation of fish myosin: Bighead carp (Aristichthys nobilis). (15th October 2019) - Gao, Ruichang; Shi, Tong; Sun, Quancai; Li, Xiuting; McClements, David Julian; Yuan, Li
Highlights: Turbidity and particle diameter of myosin decreased with Arg/His. The hydrophobicity of myosin containing Arg/His increased after two-step heating. Positively charged Arg theoretically was bound to negatively charged myosin. R-group of Arg/His might interact with unfolding aromatic residue of myosin. Arg showed a higher ability on suppressing myosin aggregation than that of His. Abstract: This research focused on the effects ofl -arginine (l -Arg) andl -histidine (l -His) on the heat-induced aggregation of fish myosin.l -Arg/l -His increased the pH of the myosin solution from 6.82 to 8.74 and 7.24, respectively, and decreased the turbidity, aggregate size, shear modulus, and breaking force. The incorporation ofl -Arg/l -His decreased the surface hydrophobicity during setting, but increased it during the two-step heating. The heat-induced aggregation of myosin was suppressed by both amino acids, with the inhibitory effect being greater forl -Arg thanl -His. On one hand, the change in the pH played a critical role in suppressing the heat-induced aggregation of myosin. On the other hand, the characteristics ofl -Arg/l -His themselves, such as net charges and particular R-groups, were another main contributor to aggregation suppression. Particularly, l -Arg/l -His could interact with exposed aromatic residues of myosin, and the interactions may dominate and overwhelm the burial of aromatic residues during two-step heating.